2014
DOI: 10.3177/jnsv.60.71
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin K<sub>2</sub> Improves Femoral Bone Strength without Altering Bone Mineral Density in Gastrectomized Rats

Abstract: Summary Gastrectomy (GX) induces osteopenia in rats. The present study examined the skeletal effects of vitamin K2 in GX rats. Thirty male Sprague-Dawley rats (12 wk old) were randomized by the stratified weight method into the following three groups of 10 animals each: sham operation (control) group; GX group; and GX1oral vitamin K2 (menatetrenone, 30 mg/kg, 5 d/wk) group. Treatment was initiated at 1 wk after surgery. After 6 wk of treatment, the bone mineral content (BMC), bone mineral density (BMD), and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Even though gut bacteria synthesize a great deal of MKs, the bioavailability of bacterial menaquinone is bad in general, and diet is the principal source of functionally available K 2 (55,70). There are studies showing that a shortterm decrease in dietary VK intake is not compensated by gut bacteria synthesized MKs (71,72). Actually, inadequate dietary intake (73), restorative proctocolectomy (74), IBD (75), liver dysfunction (76).…”
Section: Various Sources Of Vkmentioning
confidence: 99%
“…Even though gut bacteria synthesize a great deal of MKs, the bioavailability of bacterial menaquinone is bad in general, and diet is the principal source of functionally available K 2 (55,70). There are studies showing that a shortterm decrease in dietary VK intake is not compensated by gut bacteria synthesized MKs (71,72). Actually, inadequate dietary intake (73), restorative proctocolectomy (74), IBD (75), liver dysfunction (76).…”
Section: Various Sources Of Vkmentioning
confidence: 99%
“…Therefore, although intestinal microflora synthesize large amounts of menaquinones, the bioavailability of bacterial menaquinone is poor, and diet is the major source of functionally available vitamin K2 [3,7,8]. Recent studies also showed that a short-term decrease in dietary vitamin K intake is not compensated by intestinal menaquinones [22][23][24].…”
Section: Non-dietary Sources Of Menaquinonesmentioning
confidence: 99%
“…Gastroenterology Research and Practice would like to express our concern with the article titled “Influence of gastrectomy on cortical and cancellous bones in rats”, published in 2013 [1]. It was brought to our attention that a later article by the same authors published in Journal of Nutritional Science and Vitaminology in 2014 [2] used some of the same animals as in the Gastroenterology Research and Practice article, but the second article had an additional arm of rats given vitamin K and did not cite the first article. The authors did not mention in the Gastroenterology Research and Practice article that they had also used an additional arm of rats given vitamin K. In addition to the partial redundant publication, readers should be aware of the following concerns and discrepancies: In Figure 1 of Journal of Nutritional Science and Vitaminology , the gastrectomy data for all six variables are discrepant with those for the same variables in Figure 3 of Gastroenterology Research and Practice In Figure 1 of Journal of Nutritional Science and Vitaminology , the control data for work to failure in the femoral diaphysis are discrepant with those for the same variable in Figure 3 of Gastroenterology Research and Practice In the legends to Figures 1, 2, and 3 in Gastroenterology Research and Practice , the superscript letters denoting statistical significance are stated to be related to ‘versus gastrectomy' though they are above the gastrectomy data.…”
mentioning
confidence: 99%